Views of Teachers on Merging Turkish Literature and Language and Expression Courses - Melek Sultan Küçüker; Duygu Gür Erdoğan; Zeynep Demirtaş (Sakarya Üniversitesi Eğitim Fakültesi Dergisi)
The objective of this study is to determine the views of Turkish language and literature teachers about merging Turkish literature and language and expression courses. The study group of the study consists of 25 Turkish language and literature teachers working in different types of high school. In the study was conducted utilizing the case study method, one of the qualitative research methods. Data was obtained through a form consisting of semi-structured questions. The data obtained in the study were analyzed using the content analysis method. According to teachers' opinions in relation to the Turkish language and literature course, which was introduced by merging the Turkish literature and language and expression courses, it can be said that the teachers participating in the study have both positive and negative opinions in the study. Some of the opinions expressed by most of the teachers are that merging the two courses ensures subject integrity in the course, however the course duration allocated for grammar subjects is not sufficient.